Ligand-Free BaF2: Nd Nanoparticles With Low Cytotoxicity, High Stability and Enhanced Fluorescence Intensity as NIR-II Imaging Probes - Cui, Xiaoxia; Xu, Yantao; She, Shengfei; Xiao, Xusheng; Hou, Chaoqi; Guo, Haitao (Frontiers in Physics, 2021)
Ligand-free BaF2:Nd nanoparticles (NPs) with a size of 10 nm were fabricated by a novel synthetic route in the liquid phase. A transparent dispersion of the BaF2:Nd NPs mixed with propanetriol and DMSO-d6 was done. Highly stable and outstanding near-infrared (NIR) fluorescence centered at 1,058 nm was detected using an excitation wavelength of 808 nm laser. Moreover, the dispersion can be found to be stable for over 1 month, and the cytotoxicity of the BaF2:Nd NP dispersion has also been studied by 3-(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay. The superior performance of these NPs exhibits their great potential application in high-contrast and high-penetration in vivo imaging.